2020
DOI: 10.3390/cancers12061676
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis-Associated Ovarian Cancer: The Origin and Targeted Therapy

Abstract: Endometrial cysts (ECs) are thought to be the origin of endometriosis-associated ovarian cancer (EAOC). A hypothesis that the oxidative stress of iron in cysts causes “malignant transformation of ECs” has been proposed, but this has not been verified. Several population-based studies showed that endometriosis was a risk factor but did not reflect the “malignant transformation of ECs”. A review showed that most patients were diagnosed with EAOC early in monitoring following detection of ECs, and that these case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 115 publications
1
43
0
3
Order By: Relevance
“…For example, in epidemiological studies it has been observed that tubal ligation, that usually blocks tubal lumen and passage, decreases the risk for ovarian cancer [ 42 , 43 ]. Also, endometriosis has been postulated as a risk factor for ovarian cancer [ 44 , 45 ]. Inflammation due to tubal endometriosis is a known factor involved in ovarian cancer carcinogenesis, mainly through DNA mutation mediated by free radicals associated with inflammatory process [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in epidemiological studies it has been observed that tubal ligation, that usually blocks tubal lumen and passage, decreases the risk for ovarian cancer [ 42 , 43 ]. Also, endometriosis has been postulated as a risk factor for ovarian cancer [ 44 , 45 ]. Inflammation due to tubal endometriosis is a known factor involved in ovarian cancer carcinogenesis, mainly through DNA mutation mediated by free radicals associated with inflammatory process [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted to examine our hypothesis that EAOC originates from eutopic endometrium [9] and determine whether eutopic endometrium has a high frequency of mutations identical to EAOC. However, the results obtained were quite different from our predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a case of clonal lineage from eutopic endometrium to endometriosis and OCCC was reported [8]. Therefore, eutopic endometrium has recently attracted a great deal of interest as a potential origin of EAOC [9]. A previous study showed that endometrial glands are composed of monoclonal cell populations [10].…”
Section: Introductionmentioning
confidence: 99%
“…It affects approximately 10–15% of women of reproductive age, which extrapolates to around 190 million women worldwide [ 1 , 2 ]. Most affected patients often suffer from chronic pelvic pain, dyspareunia, dysmenorrhea, abnormal uterine bleeding, and infertility [ 3 , 4 ]. All these symptoms provide an impact on a patient’s quality of life, resulting in depression, anxiety, and impaired social function caused by the severity of pain [ 5 ].…”
Section: Introductionmentioning
confidence: 99%